THE EFFECT OF FINANCIAL RATIO IN PREDICTING THE CONDITION OF FINANCIAL POLICY WITH FIRM SIZE AS A VARIABLE MODERATING IN MANUFACTURING COMPANIES LISTED IN INDONESIA STOCK EXCHANGE (IDX) PERIOD 2012-2017 - Simanjuntak, Riris Trinovianti (International Journal of Public Budgeting, Accounting and Finance, 2019)
The objective of this study was to identify and analyse the effect of financial ratios in predicting financial distress conditions in manufacturing companies listed on the Indonesian stock exchange (IDX) for the period 2012-2017. The variables in this study are return on assets, current ratio, debt to equity ratio, total asset turnover and firm size. The population in this study were all manufacturing companies listed on the Indonesia stock exchange for the period 2012-2017. Sampling in this study used purposive sampling, so sample of 384 companies that met the criteria was obtained. The analytical method used in this research is descriptive statistical analysis using logistic regression analysis and interaction test to test the moderating variable. The results of this study indicate that simultaneous return on assets, current ratio, debt to equity ratio, and total asset turnover have a significant effect on predict financial distress, and firm size can moderate the effect of return on assets, current ratio, debt to equity ratio, and total asset turnover in predicting financial distress. Partially, return on assets, current ratio and total asset turnover have a negative and significant effect in predicting financial distress conditions. While the variable debt to equity ratio has a positive and significant influence in predicting the condition of financial distress. Firm Size is able to moderate the effect of Total Asset Turnover in predicting the condition of Financial Distress. However Firm Size weakens the influence of Return On Asset, Current Ratio and Debt to Equity Ratio in predicting the condition of Financial Distress.